2014
DOI: 10.1158/1078-0432.ccr-14-1019
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study of the First-in-Class Antimitochondrial Metabolism Agent, CPI-613, in Patients with Advanced Hematologic Malignancies

Abstract: Purpose The lipoate derivative CPI-613 is a first-in-class agent that targets mitochondrial metabolism. This study determined the effects of CPI-613 on mitochondrial function and defined the maximally tolerated dose (MTD), pharmacokinetics (PKs), and safety in patients with relapsed or refractory hematologic malignancies. Experimental Design Human leukemia cell lines were exposed to CPI-613 and mitochondrial function was assayed. A phase I trial was conducted in which CPI-613 was given as a 2-hour infusion o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 27 publications
1
78
0
Order By: Relevance
“…The cancer literature reports use of different protocols involving exposure of cell lines to hyperthermia from 1 hour 13 up to 3 days 3 , and some cases up for 2 weeks 14 (in most cases 12–36 h) which makes difficult to draw direct parallels between possible molecular mechanisms underlying the in vitro results and the outcomes of the human hyperthermia clinical studies. The Seahorse extracellular flux analyzer has been reported to produce valuable data measuring cancer metabolism under different experimental conditions including, but not limited to the following: testing effects on novel therapies 15–17 , changes in cancer cell substrate preferences 18–20 , effects of gene overexpression or knockdown in cancer cells 21–23 , effects of hypoxia 20, 24 and cell environmental factors 25–27 .…”
Section: Discussionmentioning
confidence: 99%
“…The cancer literature reports use of different protocols involving exposure of cell lines to hyperthermia from 1 hour 13 up to 3 days 3 , and some cases up for 2 weeks 14 (in most cases 12–36 h) which makes difficult to draw direct parallels between possible molecular mechanisms underlying the in vitro results and the outcomes of the human hyperthermia clinical studies. The Seahorse extracellular flux analyzer has been reported to produce valuable data measuring cancer metabolism under different experimental conditions including, but not limited to the following: testing effects on novel therapies 15–17 , changes in cancer cell substrate preferences 18–20 , effects of gene overexpression or knockdown in cancer cells 21–23 , effects of hypoxia 20, 24 and cell environmental factors 25–27 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this notion, other complex I inhibitors have shown efficacy as anti-tumor agents (Appleyard et al, 2012; Schockel et al, 2015) and may show selective toxicity against oncogene-ablation resistant cells (Viale et al, 2014) and cancer stem cells (Sancho et al, 2015). Additional complex I inhibitors are under development (Bastian et al, 2017), and other inhibitors of respiration or mitochondrial metabolism, including the lipoic acid derivative CPI-613 (Table 1), are currently being assessed in clinical trials (Lycan et al, 2016; Pardee et al, 2014). …”
Section: Emerging Metabolic Targetsmentioning
confidence: 99%
“…In preclinical studies CPI-613 has shown extensive anticancer effects. In a phase one study, CPI-613 has shown to be well tolerated and active in several patients with advanced myeloid malignancies [31]. In combination with chemotherapy it had encouraging activity in patients with relapsed or refractory AML especially in patients 60 years of age or older (Pardee et al in press).…”
Section: Targeting the Tca Cyclementioning
confidence: 99%